Sustainable Business Model Post-Fuel Subsidy: MSME Strategies in Adopting Green Energy Technology to Increase Efficiency and Competitiveness (Study on Culinary and Fashion MSMEs - Sylvia Sylvia; Diana Magfiroh (Al-Makki Publisher, 2023)
The revocation of fuel subsidies creates significant economic pressure on MSMEs, especially the culinary and fashion sectors, through increased operational costs that erode competitiveness. The transformation towards a sustainable business model through the adoption of green energy technology is an urgent need to build business resilience. This study aims to: (1) Analyze the impact of the revocation of fuel subsidies on the cost structure and competitiveness of MSMEs; (2) Identify the most feasible green energy technologies; (3) Formulate an integrated sustainable business model. The research uses a mixed-methods explanatory sequential approach. Quantitative data was collected through a survey of 301 MSMEs, followed by in-depth interviews and FGDs for qualitative data. Data analysis uses inferential statistics and thematic analysis. The increase in fuel increased the operating costs of culinary and fashion MSMEs by an average of 22.3% and 18.7%. Small-scale solar panels are the most technically feasible (score 4.2/5), while biomass stoves are the most economically feasible (ROI 25-35%). Successfully formulated a